ANALISIS PENERAPAN ATURAN 9 COLREG 1972 PADA ALUR PE-LAYARAN SEMPIT DI KAPAL TIRTA SAMUDRA XXXVIII - Risky Aliansyah; Rizal Rochmansyah; Achmad Ali Mashartanto; M. Kurniawan; Yusuf Pria Utama (STKIP Subang, 2026)
Maritime safety is the top priority when vessels enter narrow channels, which carry a high risk of accidents. Rule 9 COLREG 1972 serves as an important guideline, and this study analyzes its implementation on the Tirta Samudra XXXVIII – a Gen-eral Cargo vessel owned by PT. USDA SEROJA JAYA, operating on routes across Indonesia through narrow channels in Surabaya and Central Kalimantan. This re-search uses a qualitative method with data collection techniques including observa-tion, interviews, and document studies. The results show that the implementation of the rules has been well-executed: maintaining the vessel’s position on the starboard side of the channel using radar, AIS, GPS, and echo sounder; adjusting speed; con-ducting continuous observations; and communicating in accordance with regula-tions. A safety briefing is always conducted before entering the channel to anticipate potential hazards. The challenges faced include external factors (high traffic density, small vessels/fishermen obstructing the route, unfavorable weather/sea conditions) and internal factors (over-reliance on automated systems, suboptimal coordination, and varying levels of understanding among the crew). To address these issues, comprehensive measures have been taken: for external factors, the vessel monitors information from BMKG (Indonesian Agency for Meteorology, Climatology and Ge-ophysics), tide tables, and VTS (Vessel Traffic Service); reduces speed and com-municates with other vessels during heavy traffic; and uses VHF communication and evasive maneuvers when there are obstructions. For internal factors, the com-pany conducts regular training, emergency simulations, briefings, and evaluations; updates navigation equipment; and implements a closed communication system with clear roles.